Cytokine profile in the sputum of subjects with post-tuberculosis airflow obstruction and in those with tobacco related chronic obstructive pulmonary disease - Guiedem, Elise; Pefura-Yone, Eric Walter; Ikomey, George Mondinde; Nkenfou, Céline Nguefeu; Mesembe, Martha; Yivala, Mbanyamsig Mispa; Chendi, Bih Hycenta; Jacobs, Graeme Brendon; Chegou, Novel Njweipi; Okomo, Marie Claire Assoumou (BMC immunology, 2020)
Background Previous studies have shown that tuberculosis (TB) is a risk factor for chronic airflow limitation. Chronic obstructive pulmonary disease (COPD) is recognized as the result of chronic inflammation, usually related to noxious particles. Post-TB airflow obstruction and tobacco-related COPD have the same functional pathway characterized by persistent airflow limitation. We sought to compare the profile of 29 cytokines in the sputum of subjects with post-TB airflow obstruction and those with COPD related to tobacco. Results The forced expiratory volume in the first second (FEV1) and forced expiratory volume/forced vital capacity (FEV/FVC) ratio were lower in the COPD patients with the history of smoking compared to the post-TB airflow obstruction subgroup. The stages of the disease were more advanced in COPD / tobacco patients. Among the cytokines, IL-1α, IL-1β, MIP-1β, sCD40L and VEGF levels were higher in COPD patients, compared to the controls with p values ​​of 0.003, 0.0001, 0.03, 0.0001 and 0.02 respectively. When the two COPD subgroups were compared, IL-1α, IL-6, TNF-α and IL-8 levels were higher in the COPD patients with the history of tobacco compared to the COPD patients with the history of TB with p -values ​​of 0.031, 0.05, 0.021 and 0.016, respectively. Conclusion COPD related to tobacco is more severe than post-TB airflow obstruction. The pathogenesis of post-TB airflow obstruction appears to involve the cytokines IL-1RA, IL-1α, IL-1β, IL-17, GRO and sCD40L, while COPD related to tobacco involves more cytokines.